A Phthalocyanine‐Based Glutathione‐Activated Photosensitizer with a Ferrocenyl Boron Dipyrromethene Dark Quencher for Photodynamic Therapy. Issue 10 (2nd October 2019) - Shi, Wen‐Jing; Ng, Dennis K. P.; Zhao, Shirui; Lo, Pui‐Chi
Abstract: The front cover artwork is provided by the Dennis K. P. Ng group from the Chinese University of Hong Kong, and the Pui‐Chi Lo group from the City University of Hong Kong. The image illustrates the activation of a phthalocyanine‐based photosensitizer through cleavage of the disulfide linker by intracellular glutathione (GSH) and separation from the ferrocenyl boron dipyrromethene‐based dark quencher. Read the full text of the Article at 10.1002/cptc.201900115 . Abstract : "Dark quenchers are a crucial component in fluorescence resonance energy transfer based bioprobes. We developed a near‐infrared‐absorbing ferrocenyl boron dipyrromethene that could be used as a dark quencher for a glutathione‐activated phthalocyanine‐based photosensitizer. The glutathione‐responsive properties were studied in aqueous media and inside cancer cells. The activation in fluorescence emission was also demonstrated in tumor‐bearing nude mice…" This and more about the story behind the front cover can be found in the Article at 10.1002/cptc.201900115 .